See you in Chechnya - Kvatashidze, Alexander (Georgia Estonia France Germany, 2016)
After falling in love with a French photographer, a young Georgian man follows her to war in Chechnya and puts himself into the shoes of a war reporter.
Verzio Film Festival Submission
Keywords: Documentary films